2022
DOI: 10.21659/rupkatha.v14n2.16
|View full text |Cite
|
Sign up to set email alerts
|

Art and Culture in the Diplomatic Ceremonial as the Basis of International Relations

Abstract: Currently, there is an increased interest in ceremonial culture. A ceremonial is a kind of cultural message from one social group of people to another. The basic idea of behaviour, the inner meaning of secular ceremonial is laid down in church rituals, and external forms of behaviour can be borrowed from the traditions of everyday secular life. Diplomacy as one of the spheres of applied politics is a very complex and responsible type of human activity, which has always had a pronounced ritual character. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…145-146) Ancient people are commonly known to perform rituals of idol worship as a form of customs carried out by the community, in which they believed that the idols could grant their wishes. Furthermore, this kind of ceremony is considered a culture embraced by social groups (Zakharova, 2022). A study on a similar topic conducted showed that THEORY AND PRACTICE IN LANGUAGE STUDIES the relevance of cultural practices allowed the creation of sustainable indigenous wisdom (Rivera, 2019).…”
Section: A Resultsmentioning
confidence: 99%
“…145-146) Ancient people are commonly known to perform rituals of idol worship as a form of customs carried out by the community, in which they believed that the idols could grant their wishes. Furthermore, this kind of ceremony is considered a culture embraced by social groups (Zakharova, 2022). A study on a similar topic conducted showed that THEORY AND PRACTICE IN LANGUAGE STUDIES the relevance of cultural practices allowed the creation of sustainable indigenous wisdom (Rivera, 2019).…”
Section: A Resultsmentioning
confidence: 99%
“…The study by O. Zakharova (2022) identifies art as a communicative factor not only in classical, but also in public diplomacy. This suggests that art can be used to communicate messages and ideas between countries and cultures during international sports ceremonies.…”
Section: Introductionmentioning
confidence: 99%